IMPLEMENTASI SISTEM PENGELOLAAN SARANA DAN PRASARANA BERBASIS WEBSITE DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) UNTUK PENENTUAN PRIORITAS(STUDI KASUS: KELURAHAN DESA BANDASARI) - Firdaus Muzayyin; Slamet Wiyono; Zaenul Arif (INTECOMS: Journal of Information Technology and Computer Science, 2026)
Manual management of facilities and inventory often leads to difficulties in data retrieval, reporting, and determining asset maintenance priorities. This issue is experienced by the Bandasari Village Office, Dukuhturi District, Tegal Regency, which lacks an integrated inventory management system. This study aims to develop a web-based Facilities and Inventory Management Information System by implementing the Simple Additive Weighting (SAW) method to support asset maintenance prioritization. The research employed the Research and Development (R&D) approach, consisting of problem identification, data collection, system design, implementation, and testing. The system was developed using the Laravel framework with MySQL as the database management system. Functional testing was conducted using the Black Box Testing method to ensure that all system features met user requirements. The results indicate that the developed system successfully integrates inventory management, procurement, maintenance, asset transfers, and reporting into a single web-based platform. Furthermore, the implementation of the SAW method generates objective maintenance priority rankings, enabling more effective and transparent decision-making. Black Box Testing confirmed that all core system functions operated as intended without significant errors. Therefore, the proposed system improves the effectiveness, efficiency, and accuracy of facilities and inventory management at the Bandasari Village Office while supporting more systematic and data-driven asset maintenance decisions.